Risk stratification in pediatric hypertrophic cardiomyopathy: Insights for bridging the evidence gap?. (June 2018) - Nakano, Stephanie J.; Menon, Shaji C.
Abstract: Identification of children with hypertrophic cardiomyopathy (HCM) who are at high risk for sudden cardiac death (SCD) remains challenging. Although a large number of risk factors have been implicated in HCM associated SCD, evidence for individual risk factors are not robust. Current risk prediction models are extrapolated from adult HCM and have low positive predictive value when applied to the pediatric HCM population. Clinical factors that are strongly associated with SCD in children with HCM are limited to previous adverse cardiac event, prior syncope and extreme left ventricular hypertrophy; there are variable conclusions regarding the utility of other conventional risk factors. Additionally, while implantable cardioverter defibrillators (ICDs) are effective in aborting malignant arrhythmias, ICD complication rates are higher in children than in adults. Although echocardiography derived parameters like left atrial volume, diastolic function indices, severity of left ventricular outflow tract obstruction and abnormalities in deformation imaging (strain and strain rate) have been associated with SCD risk in childhood HCM, these echocardiographic predictors have low specificity and sensitivity. More recently, cardiac magnetic resonance (CMR) imaging derived perfusion and viability (delayed gadolinium enhancement) abnormalities have been associated with SCD in childhood HCM and warrant further investigation. Given that myocyte disarray and fibrosis are prominent histological features of HCM, novel imaging modalities that allow for improved tissue characterization may provide additional insight into HCM phenotypes that are at higher risk for SCD. T1 mapping, cardiac diffusion tensor imaging (cDTI), and assessment of a phosphocreatine/adenosine triphosphate (PCr/ATP) ratio by 31 P magnetic resonance spectroscopy ( 31 P-MRS) are future avenues of myocardial imaging that may provide additional prognostic benefit when used in conjunction with traditional assessments. Further investigations of disease pathogenesis, genotype-phenotype correlations, genetic modifiers and circulating biomarkers specific to children with HCM hold promise for a more effective and refined risk stratification model in pediatric HCM. Highlights: Sudden cardiac death (SCD) risk stratification of children with hypertrophic cardiomyopathy (HCM) remains challenging. Current risk prediction models in pediatric HCM are extrapolated from adult HCM and have low positive predictive value. Larger studies aimed at improving over understanding of risk factors for prevention of SCD in childhood HCM are needed. Novel and emergent imaging modalities, especially CMR imaging, can assist in improving prediction of SCD in childhood HCM.